Improving Bovine Embryo Development and Quality Using Bovine Oviductal Epithelial Cell‐Derived Conditioned Medium (bOEC‐CM) - Saeed Kazemi Hosseinabadi; Hassan Nazari; Mehran Arabi; Naser Shams Esfandabadi; Ebrahim Ahmadi; Azita Afzali; Hamidreza Ghanaei (Veterinary Medicine and Science)
ABSTRACT Background The embryo co‐culture systems with the monolayer cultured cells are complex, unreproducible, and have a high probability of biological contamination. Therefore, nowadays, using conditioned media is a suitable alternative to these methods. Objectives This study aimed to investigate the impact of utilizing bovine oviductal epithelial cell‐derived conditioned medium (bOEC‐CM) on subsequent embryo development and quality. Methods Bovine embryos produced in vitro were cultured in a specific medium supplemented with either 5% charcoal‐stripped FBS (Charcoled Strip Serum [CSS]) or 10% bOEC‐CM from either Days 1 or 3 post‐fertilization. Various parameters, such as cleavage rate, blastocyst formation, hatching rate and blastocyst quality, were assessed. Results The results indicated that adding 10% CM from Day 1 significantly reduced the cleavage rate compared to using CSS on the same day (p < 0.05). Furthermore, the CSS and CM from both Days 1 and 3 increased blastocyst formation rates (p < 0.05). Notably, the addition of 10% CM on Day 3 significantly improved the hatching rate compared to the other groups (p < 0.05). Both CM and CSS were found to enhance the inner cell mass (ICM), trophectoderm (TE) and total cell numbers in blastocysts when used on both Days 1 and 3 (p < 0.05). Additionally, CM from Day 3 positively influenced the expression levels of development‐specific genes in cultured embryos (p < 0.05). Conclusion Overall, the findings suggest that using bOEC‐CM at a 10% concentration may provide a promising supplement even better than serum and traditional co‐culture methods during the last 5 days of embryo culture.